THE PSYCHO-SOCIAL CIRCUMSTANCES OF CAR GUARDS: INTERVENTIVE ROLES OF THE SOCIAL WORKER - Strydom, Herman; Strydom, C (Social Work/Maatskaplike Werk, 2004)
In South Africa unemployment is a major problem and many people are desperate to make an earnest living and are prepared to do any job as long as it brings in enough money for a roof over their heads and food on the table. Crime has become a major social problem within the South African society and motor vehicle thefts and car burglaries are high on the list of crime statistics. Police and security protection services are unable to keep guard over all the parking areas and informal car guards did not provide the answer. To address this problem, car watch organisations were introduced in the city centers. Social workers should identify those people who are especially vulnerable, including car guards, and ensure that their abilities and potential are developed and strengthened. The objective of the research project was to study the survival skills of car guards relating to their economic and social circumstances. The phenomena of difficult customers, dangerous and harsh working conditions, and poor remuneration were investigated. A qualitative study accompanied by a phenomenological research design was implemented for the study. Field research and specifically in-depth personal interviewing and naturalistic observation were used as research procedures.